Institutionalizing Health Technology Assessment and Priority Setting in South Korea's Universal Health Coverage Journey - Juhwan Oh; Min-Jeong Kim; Sujeong Hur; Juyeon Oh; Dong-Sook Kim (Taylor & Francis Group, 2023)
This study charts the chronological developments of the three institutions that were established in South Korea for priority setting in health. In 2007, the Evidence-based Medicine Team and the Center for New Health Technology Assessment (CnHTA) were established and nested in the Health Insurance Review and Assessment Service (HIRA). In December 2008, the National Evidence-based Healthcare Collaborating Agency (NECA) was launched, to which the CnHTA was transferred in 2010. Since then, non-drug technologies have been reviewed by NECA and drugs have been reviewed by HIRA. Political debates about how to embrace expensive but important health technologies that were not on the benefits list led to the creation of the Participatory Priority Setting Committee (PPSC) in 2012. The PPSC, led by the general public, has played a key role in advancing the path toward universal health coverage by revitalizing the list of essential, yet previously overlooked, medical technologies. PPSC offers these technologies a second chance at coverage. HIRA and NECA served to strengthen evidence-based and efficiency-based decision-making in the health system via CnHTA, and PPSC served to strengthen social value-based decision making via priority setting in Korea. The reassessment by PPSC may be relevant in countries where the economy is growing and citizens want to rapidly expand the benefits list.